Research progress of the role and application of polyunsaturated fatty acid metabolites in oral diseases - XU Huaxing, WEI Xiaoling (Editorial Office of Stomatology, 2024)
This review aims to explore research progress ofthe role and application of polyunsaturated fatty acid (PUFA) metabolites in oral diseases. We first briefly review the metabolic pathways and key enzymes of PUFAs, as well as their biological functions. Then, we discuss in detail the role of PUFA metabolites in various oral diseases, including oral mucosal diseases, periodontal diseases, dental and pulp diseases, oral cancer, and temporomandibular joint disorders (TMD). Studies have shown that PUFA metabolites play an important role in regulating inflammation, immune responses, and tissue repair, and are closely involved in the development and progression of oral diseases. Moreover, PUFA metabolites have potential application value in the diagnosis, treatment, and prevention of oral diseases. Therefore, research on the role and application of PUFA metabolites in oral diseases will help deepen our understanding of the pathogenesis of oral diseases and provide new ideas and methods for clinical treatment of oral diseases.